2014
DOI: 10.1017/idm.2014.9
|View full text |Cite
|
Sign up to set email alerts
|

Breaking the web of needless disability

Abstract: Background: In 2012 I presented a program to the London IFDM entitled “Breaking the Web of Needless Disability”. The model drew heavily from the latest neuroscientific theory, and was quite well received. This program represents further development of the ideas presented in London to encompass “resilience”.Hypothesis: 1. “Resilience” is a behaviour that is learned and unlearned like any other skill; 2. Understanding how humans think and react in compensation systems will yield valuable insight into the buildin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 62 publications
0
3
0
Order By: Relevance
“…Many stakeholders are involved in the management of individuals with work-related musculoskeletal pain, which in itself can be a barrier to the efficient management of 5 injured workers (13)(14)(15)(16). Effective communication amongst these stakeholders can be a factor associated with improved work rehabilitation outcomes (16)(17)(18)(19)(20), particularly in complex cases and/or where there is delayed recovery.…”
Section: Introductionmentioning
confidence: 99%
“…Many stakeholders are involved in the management of individuals with work-related musculoskeletal pain, which in itself can be a barrier to the efficient management of 5 injured workers (13)(14)(15)(16). Effective communication amongst these stakeholders can be a factor associated with improved work rehabilitation outcomes (16)(17)(18)(19)(20), particularly in complex cases and/or where there is delayed recovery.…”
Section: Introductionmentioning
confidence: 99%
“…Many aspects of mental and behavioral health are typically assessed by self-report as compared to using more objective, external measures of mental health [7]. Complicating this issue further, previous literature introduces reasons for potential reporting bias of self-reported disability – typically assumed to be in the direction of individuals over reporting their disability level [8,9]. …”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, our discourse analysis of vocational rehabilitation in New Zealand identified that there is a significant danger of 'failure' in mainstream vocational rehabilitation for people whose work (re)entry is not fast and straightforward, which can occur for a variety of reasons including complicated interpersonal relationships at work and other what is termed 'psychosocial' reasons. In a sense then, perpetuating a system of vocational rehabilitation that defines successful resumption of work-ability in such a narrow way can be argued to actually produce ongoing work-disabilityclassifying people who do not achieve that definition of success as 'off track', 'complex', or 'difficult' which in turn affects their understandings of (and responses to) their own situation [19,39].…”
Section: Disability Studies' Critiques Of Normative Judgements In Rehmentioning
confidence: 99%